Application of Big Data Visualization in Urban Planning. Issue 4 (February 2020) - Cao, Xinhui; Wang, Mei; Liu, Xin
Abstract: During the past ten years, with the process of urbanization accelerates, urban population has increased sharply. Traffic congestion, noise pollution, garbage treatment and other problems, which make the traditional urban planning methods difficult to shoulder this heavy responsibility. At the same time, intelligent city and the construction of informationize is also developing rapidly, the practice and research of big data in urban planning industry are widely used. Large scale data visualization is one of the most important steps in big data. Not only can the data be expressed in visible form to improve the efficiency of data analysis, but also human-computer interaction can be carried out. To overcome these problems, this paper studies the problem of urban planning based on large scale data visualization. Firstly, it extends the concept and model of big data visualization to the significance and framework of applying big data visualization to urban planning. Then through the case of visualization of traffic data and environmental sound data, we can see that both quality and efficiency have been significantly improved. Furthermore in order to stimulate future research in this field, we also highlight the major opportunities and challenges, as well as potential important research directions for urban planning.